Granulomatosis with Polyangiitis (GPA) in a 15-year-old Girl with Facial Acne-like Ulcers: A Case Report - Jamali Moghadam, Saeed R.; Salehi, Mohammad Reza; Mojtahedi, Seyed Yousef; Fadaei, Narges; Dadras, Omid; SeyedAlinaghi, SeyedAhmad; Mohammadifirouzeh, Mona (Infectious Disorders - Drug Targets, 2020)
Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis (WG), is a multisystem autoimmune disease of unknown etiology often misdiagnosed as pneumonia. The hallmark features include necrotizing granulomatous inflammation and pauci-immune vasculitis in small and medium-sized blood vessels. We described a 15-year-old female with a history of six months of acne-like facial and peri-auricular lesions. She had received conventional treatment for acne (antibiotics + topical corticosteroid) with no response. She also had a history of chronic coughs, which always diagnosed and treated as sinusitis. In addition, she had a history of frequent dysuria, which always diagnosed and treated as a urinary tract infection. Given the history, with suspicion of a multi-systemic disease such as vasculitis; we performed some diagnostic laboratory and radiologic tests in order to rule out the possible etiologies. The results were positive for cytoplasmic anti-neutrophil cytoplasmic antibody (C-ANCA). The urine analysis suggested the involvement of kidney micro-vasculature. In addition, two nodular lesions with the cystic pattern were observed in the CT scan of the lungs. However, the skin and nasal biopsies revealed no evidence of chronic necrotizing vasculitis or granulomatous lesion. Nonetheless, treatment was initiated with a strong suspicion of GPA. Following the treatment, the patient's symptoms completely disappeared, and the diagnosis of GPA was confirmed.
Keywords: C-ANCA